A review on catalytic CO2 pyrolysis of organic wastes to high-value products - Prakash Parthasarathy (10159511) (2023)
As an alternative to conventional pyrolysis, CO2-assisted pyrolysis is ideal for treating organic waste materials such as plant biomass, animal manure, domestic and municipal wastes as the usage of CO2 facilitates the decomposition of materials and inhibits the formation of many harmful chemical compounds. The application of catalysts in CO2 pyrolysis has been viewed as a way to valorise waste on a large scale. This article provides insight into the advantages of using CO2 and catalysts in pyrolysis and a list of catalysts currently used in CO2 pyrolysis. The main purpose of this review is to summarise the findings of recent analyses of catalytic CO2 pyrolysis of wastes. The study also discusses the different procedures involved in catalyst preparation and provides a broad review of the effects of catalytic CO2 pyrolysis on pyrolysis products’ quantity and quality. The article concludes by evaluating the competency level of catalytic CO2 pyrolysis technology and providing an overview of the technique's current challenges and future recommendations. The review is in line with fostering the usage of CO2 to meet CO2 emission regulations outlined by the 2015 Paris Agreement. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2022.127073